Engaging the student voices to improve referencing skills and practices in higher education: A South African case study - Singh, D.; Steenkamp, M.; Harmse, T.; Botha, J.C. (South African Journal of Higher Education, 2020)
Acknowledging that plagiarism includes many different behaviours, this study focusses on one specific plagiarism challenge, namely, acts of incorrect referencing and citation (sometimes called technical plagiarism). Notwithstanding anti-plagiarism policies being in place with penalties for a breach of the rules, Referencing Guides shared with students, additional workshops and tutorial sessions to facilitate the students' understanding of the Institution's referencing rules and standards, higher education institutions continue to experience an ongoing increase in the number of (technical) plagiarism cases, including repeat offenders. While the importance of proper referencing skills and techniques is fundamental to sound scholarship, a further concern is the impact of the accruing penalties on student success, retention, and graduateness. This study actively engaged the students, requiring them to reflect on their prior experiences with various sources of information, as well as their understanding and appreciation of how, why, what, and when to reference the resources used in their studies. The study discovered that students often describe the Institution's approach to teaching the skills of referencing as “alienating” and “punitive” and antithetical to learning. Based on the research data, and comparing the outcomes from other similar research studies, the paper propose leading practices that will support higher education institutions better prepare students, especially students of the Alpha Generation, for improved understanding and application of institutional norms for academic referencing and citation practices.